EFEKTIVITAS WEWENANG POLISI DALAM MENANGANI TINDAK PIDANA KORUPSI DI INDONESIA - Putri Afra Salsabila; Shinda Zahra Gelista; Sulistiasih (JOURNAL OF LAW AND NATION, 2024)
Corruption is a major problem in Indonesia that hinders economic and social progress, undermines the integrity of government, and erodes people’s trust in government. The police have the authority to investigate and arrest people who commit corruption. This study aims to assess how effective the police are in handling corruption crimes in Indonesia. The method used is reviewing literature from various reliable references. The research shows that although the police play a significant role in combating corruption, many problems such as limited resources, political pressure, and complex cases hinder law enforcement. To improve the ability of the police to handle corruption cases, it is necessary to improve agency coordination, use of technology, and public support.